Understanding Tourists’ Emotions in Time and Space: Combining GPS Tracking and Biosensing to Detect Spatial Points of Emotion - Reif, Julian; Schmücker, Dirk (Journal of Tourism, Sustainability and Well-being, 2021)
The main contribution of the study is to provide a new methodological and analytical approach in conceptualising and measuring spatial points of emotion (SPoE). It contributes to the further development of mobile methods in applied tourism geography. A mixed-methods design, including georeferenced biosensing data and contextual information, such as video data and ex-post interviews, was used to examine positive SPoE. A conceptual framework was developed for measuring SPoE. The results showed that georeferenced biosensing indicators can be used to identify SPoE in a tourism setting. Using a data-driven and episode-driven approach, visitors’ points of relaxation at the beach can be identified. However, there are some limitations to the method, as the interpretation of biosensing signals in a real-world situation needs further clarification. Validly identifying positive valences should be a focus in future tourism research.